(untitled) (REMUNOM, 2025)
The current work sought to analyze, through a bibliographic review, what results teachers and researchers have achieved with the use of mind maps in the classroom. Therefore, this study presents a state of knowledge on school practices involving mind maps, with an analysis of research in which this method was applied with students. Therefore, the procedure used to develop the study was a state of knowledge bibliographic research, with a qualitative approach and exploratory character. For data collection, the search platform “Periódico Capes” was used with the descriptors “Mapas Mentais and Educação”. The time frame was from 2019 to 2024, among other filters described in the methodology section. Regarding the analysis, content analysis was chosen, based on the following pre-categories: article title; authors (year); target audience; practice developed; main results obtained. For the latter, other categories emerged, which constitute the results of this research. Therefore, as main results, it is possible to affirm that mind maps can contribute significantly to the teaching and learning process. The emerging categories of the studies analyzed are: engagement and active participation of students; improvement in the organization of thought and structuring of ideas; improvement in connections between concepts; aid in memorization, understanding of content and consolidation of knowledge; development of creativity and critical thinking; transition from mechanical learning to meaningful learning; awareness of students to better understand their realities and the context in which they live.